Advanced microfluidic and 3D cell culture platforms for modeling vascularization in diabetic foot ulcers: A systematic review of translational challenges and perspectives - Ana Karoline Almeida da Silva; Gustavo Adolfo Marcelino de Almeida Nunes; Rafael Mendes Faria; Klériston Santos; Rafael Pissinati de Souza; Lindemberg Barreto Mota da Costa; Marcos Augusto M. Fonseca; Sheila Sousa Gomes Fortes; Amanda Maciel Lima; Isolda Monteiro; Pedro Henrique Almeida; Ana Carolina Migliorini Figueira; et al. (PLoS ONE, 2026)
The healing process of diabetic foot ulcers (DFUs) presents a slow pattern with an increased risk of infections, ischemia, and thrombosis correlated with high levels of reactive oxygen species production. Vascular injury is one of the factors contributing to the difficulty of wound healing in diabetic patients. Although the understanding of the pathophysiology of DFUs has significantly increased in recent years, associated treatments still have a high level of failure, leading to high morbidity rates, mortality, and amputations. Three-dimensional (3D) cell culture platforms offer a new approach to investigating and treating these wounds, as they can reproduce one or more physiological systems in a relevant microenvironment. This systematic review describes the advancements, challenges, and future implications of advanced 3D culture models in vascularization, encompassing pathophysiological understanding, treatment, and prognostic perspectives. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. This work was registered under PROSPERO protocol number CRD42022336473. The eligibility criteria addressed studies related to chronic DFUs that analyzed vascularization during the healing process. The selected study designs involved 3D cultures and organ-on-a- chip (OoC) platforms, utilizing either primary or secondary human cell lines. Studies published more than 10 years ago or using only animal cells in 2D culture environments were excluded. The search was conducted in PubMed, LILACS, Embase, MEDLINE, IEEE, the BSV regional portal, ScienceDirect, Scopus, CINAHL, EBSCO, and Web of Science. A total of 2,539 relevant studies were identified as of June 1, 2025. After screening, only seven met the inclusion criteria. These studies reflect a growing interest in using hydrogel scaffolds and microfluidic systems to replicate diabetic skin environments; however, the field remains in an early stage of development. OoC platforms, in particular, stand out for their ability to recreate dynamic, tissue-like conditions and vascular function. While some promising attempts have been made to combine hydrogels with these technologies, the evidence is still limited and inconclusive for chronic wound modeling. This review underscores both the potential and the urgent need for more robust and translational research in this area—especially toward building personalized, clinically relevant models to support future drug testing and therapeutic innovation.